Pooh's wishing star - Talkington, Bruce; Kurtz, John.; Milne, A. A. (New York : Disney Press, 1997)
After Pooh learns about making wishes on stars, he tells all his friends so that they can make wishes, too.
"Based on the Pooh stories by A.A. Milne"--Verso of t.p.
At head of title: Disney's.
Keywords: Wishes; Friendship; Teddy bears; Toys